2021
DOI: 10.1182/bloodadvances.2020003475
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized mitochondrial DNA released after inflammasome activation is a disease biomarker for myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are heterogeneous hematopoietic stem cell malignancies that can phenotypically resemble other hematologic disorders. Thus, tools that may add to current diagnostic practices could aid in disease discrimination. Constitutive innate immune activation is a pathogenetic driver of ineffective hematopoiesis in MDS through Nod-like receptor protein 3 (NLRP3)–inflammasome-induced pyroptotic cell death. Oxidized mitochondrial DNA (ox-mtDNA) is released upon cytolysis, acts as a danger si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Recent data have suggested that damage-associated molecular pattern (DAMP)induced inflammation (via oxidized mitochondrial DNA) in the BM of MDS patients can lead to the uncontrolled activation of inflammasome machinery, causing HPSC lytic cell death mediated via pyroptosis, and this can act as a pathogenetic driver of ineffective haematopoiesis in MDS (Figure 2). The levels of oxidized mitochondrial DNA were reported to be highest in MDS compared with other overlapping syndromes and reactive conditions, such as CMML, ChIP, and anaemia [176]. Furthermore, mesenchymal niche can also induce genotoxic stress through p53-S100A8/9-TLR4 inflammatory signalling pathway which directly induces mitochondrial dysfunction, oxidative stress, and the activation of DNA damage responses in HSPCs159.…”
Section: Bmme Inflammation: a Friend Or A Foementioning
confidence: 99%
“…Recent data have suggested that damage-associated molecular pattern (DAMP)induced inflammation (via oxidized mitochondrial DNA) in the BM of MDS patients can lead to the uncontrolled activation of inflammasome machinery, causing HPSC lytic cell death mediated via pyroptosis, and this can act as a pathogenetic driver of ineffective haematopoiesis in MDS (Figure 2). The levels of oxidized mitochondrial DNA were reported to be highest in MDS compared with other overlapping syndromes and reactive conditions, such as CMML, ChIP, and anaemia [176]. Furthermore, mesenchymal niche can also induce genotoxic stress through p53-S100A8/9-TLR4 inflammatory signalling pathway which directly induces mitochondrial dysfunction, oxidative stress, and the activation of DNA damage responses in HSPCs159.…”
Section: Bmme Inflammation: a Friend Or A Foementioning
confidence: 99%
“…This clearly indicates a great potential for developing or re-tasking drugs for treating these systemic inflammatory diseases associated with mitochondrial energetics and metabolism. Additionally, new biomarkers of the mitochondrial nucleic acid sensing pathways could accelerate timely detection and life-saving therapeutic interventions (Borsche et al, 2020;Ward et al, 2021). Hence, it is necessary to have a comprehensive overview of the mitochondrial nucleic acid sensing pathways in order to study diseases of the OXPHOS dysfunction.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…As re-introduced oxidized DNA can activate NLRP3 regardless of its origin, it is likely that NLRP3 senses the presence of 8-OH-dG within ox-mtDNA. Ward et al reported an increased secretion of ox-mtDNA, following inflammasome activation in an in vitro cancer model [ 49 ].…”
Section: Mtdna As a Danger Signalmentioning
confidence: 99%